2010
DOI: 10.1149/1.3481711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SEI on Capacity Losses of Spinel Lithium Manganese Oxide/Graphite Batteries Stored at 60°C

Abstract: The discharge capacities of spinel-type Li 1.1 Mn 1.9 O 4 /graphite cells charged in electrolytes with solid electrolyte interphase ͑SEI͒-forming additives are investigated after being stored at 60°C. The presence of Mn deposits on the anode surface, which is responsible for the capacity fading of cells, is clearly shown by means of open-circuit voltage, ex situ X-ray diffraction, and energy-dispersive spectrometry measurements. Unlike fluoroethylene carbonate, using vinylene carbonate as an SEI former leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 12 publications
0
88
0
Order By: Relevance
“…• C. [29][30][31] These metal ions then deposit on the anode surface by taking the electrons from the lithiated graphite anode. This electron consumption via the metal reduction on the lithiated graphite anode results in an increase in the anode potential and thus a decrease in the full cell potential.…”
Section: Resultsmentioning
confidence: 99%
“…• C. [29][30][31] These metal ions then deposit on the anode surface by taking the electrons from the lithiated graphite anode. This electron consumption via the metal reduction on the lithiated graphite anode results in an increase in the anode potential and thus a decrease in the full cell potential.…”
Section: Resultsmentioning
confidence: 99%
“…4,16 Two main routes by which capacity fading may occur due to dissolution are (i) structural changes to the positive electrode and leading to reduced insertion capacity and (ii) accelerated growth of the SEI layer at the negative electrode and the resulting irreversible Li consumption. 15,[17][18][19][20][21][22] Capacity fade due to the structural changes occurring in the positive electrode during partial dissolution is more likely in spinel electrodes, where the extent of dissolution is high, or at high potentials (overcharge). This large degree of dissolution in spinels may cause shrinkage of the active material, which decreased the effective transport properties and kinetics of the electrode.…”
Section: 7-14mentioning
confidence: 99%
“…They also reported that structural stability is directly related to the extent of dissolution in electrodes. 18 Dissolution may also cause a decrease in cell capacity by increased growth and breakdown of the SEI layer 21,22 on the negative electrode. Although dissolution has been studied extensively in spinel electrode materials and its negative effects on cell capacity have been wellestablished, how dissolution affects the growth of the solid electrolyte interphase (SEI) layer is not well-understood.…”
Section: 7-14mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition different mechanisms on the cathode side are known for calendric aging. In literature, different materials with different aging behaviors are known, especially deactivation of active material, dissolution of particles and side-reactions of active material [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%